AL-AHRUF AS-SAB‘AH AND ITS RELATIONSHIP WITH AL-QIRÂ’ÂT; Theory and Refutation of Orientalist Criticism of the Qur’an: AL-AHRUF AS-SAB‘AH DAN KAITANNYA DENGAN AL-QIRÂ’ÂT; Teori dan Sanggahan Atas Kritik Orientalis Terhadap Al-Qur’an - Abdul Hakim; Oka Putra Pratama (Takwil: Journal of Quran and Hadith Studies, 2022)
This article aims to determine the nature of al-ahruf as-sab‘ah and al-qirâ’ât. In addition, this article also refutes some orientalist criticisms and negative accusations against the Qur’an by referring to the opinions of classical and contemporary scholars. This article uses a qualitative research method with the type of library research. The approach used is the interpretation approach and ulum al-Qur’an. This study found that al-ahruf as-sab‘ah was originally a rukhsah given to Muslims at that time because many Muslims had difficulty reading the Qur’an with one kind of letter. However, the rukhsah is removed after the loss of excuse. At the time of Caliph Uthman, the Qur'an was written and recorded only qirâ’ât following the Quraish lahjah (dialect) and left other qirâ’ât to avoid disputes in the reading of the Qur’an. The bookkeeping and writing of the Qur'an at the time of Caliph Uthman was carried out very carefully with high accuracy and witnessed by many friends who memorized the Qur'an and were following al-‘ardhah al-akhîrah. This refutes the orientalists who doubt the authenticity of the Qur’an by accusing the existence of negligence, political motives, the banishment of some al-ahruf as-sab‘ah, different qirâ’ât, and Arabic writing.